Trophy Hunters & Crazy Cat Ladies: exploring cats and conservation in North America and Southern Africa through intersectionality. Issue 9 (2nd September 2021) - McCubbin, Sandra G.; Van Patter, Lauren E.
Abstract: What explains the silencing, dismissal, disavowal, ridicule, and stigmatizing of care for individual animals observed in conservation discourses? We examine this question using a comparative case study of feral cat management in North America and lion conservation in southern Africa. We apply intersectionality to illustrate the ways in which hierarchies of scale (individual/population), knowledge (emotion/reason), and gender (feminine/masculine) marginalize concern for individual animals, with consequences for the lives of animals and those who care for them. We explore the embodiment of these intersecting hierarchies in two contrasting, yet entangled, figures – the othered Crazy Cat Lady and the privileged Trophy Hunter – which serve to illustrate how mainstream conservation discourses position care for animals as feminine and emotional, while privileging a very different human-animal relationship based in masculine, rational concern for species. Overall, we contribute to efforts in feminist more-than-human scholarship by: extending intersectional analysis to empirical cases of animal conservation and management where it has had limited application; applying intersectionality to manifestations of social power other than categories of identity by considering gender alongside hierarchies of scale and knowledge; and, examining both othered and privileged identity formation by employing a comparative case study approach. We conclude by highlighting alternate ontologies which hold promise for fostering more equitable, less hierarchical visions of multispecies flourishing which avow care for individual animals.